T108. AUT00206, A NOVEL KV3 CHANNEL MODULATOR, REDUCES KETAMINE-INDUCED BOLD SIGNALLING IN HEALTHY MALE VOLUNTEERS: A RANDOMISED PLACEBO-CONTROLLED CROSSOVER TRIAL. (9th April 2019) - Deakin, Bill; Perini, Francesca; Nazimek, Jadwiga; McKie, Shane; Hutchison, John; Alvaro, Guiseppe; McFarquhar, Martyn; Turgut, Tolga; Sajjala, Anil; Lovick, Susan; Dourish, Colin; Large, Charles
Abstract: Background: Evidence suggests that schizophrenia involves impaired functioning of fast spiking (FS) GABA interneurons and disinhibition of glutamate release. Acute ketamine disrupts interneuron-pyramidal neuron balance, increases network activity, and increases the cortical blood oxygen level dependent (BOLD) signal in magnetic resonance imaging (MRI) studies in rodents and humans. In humans, ketamine markedly increased BOLD signal in dorsal anterior cingulate (dACC) and in precuneus, which correlated with psychosis–like subjective effects of the drug. These effects were reduced by pre-treatment with lamotrigine (Deakin et al PMID:18250253). AUT00206 is a positive modulator of Kv3.1 and Kv3.2 channels that are located on fast-spiking cortical GABA interneurons. We have previously reported that AUT00206 reduced the BOLD response to acute ketamine in rodents. The present study explored the effects of AUT00206 in an acute ketamine challenge study in healthy volunteers. Methods: The design was a single-centre, double-blind, placebo-controlled, crossover study for 16 healthy participants. AUT00206 (800 mg, 2000 mg) or placebo was administered 4 hours prior to the intravenous infusion of ketamine or saline during MR BOLD imaging. Saline was infused for 8 minutes (baseline), followed by ketamine (bolus of 0.26 mg/kg for 1 min, maintenance of 0.25 mg/kg/h for 30 mins) or continued saline. The BOLD signal was followed for a further 16 mins. Participants attended 4 pharmaco-MRI sessions in which they received (in random order) placebo + saline, placebo + ketamine, 2000 mg AUT00206 + ketamine, 800 mg AUT00206 + ketamine. BOLD signal was averaged within 3 ROIs (dACC, precuneus and thalamus). A mixed models ANCOVA examined the influence of Treatment (4 levels) and Time (2 levels: the average BOLD signal over the first and second 8 minutes of the active infusion). The baseline average was used as a covariate. The doses and ROIs were analysed separately. Within the model, pairwise contrasts of interest were AUT00206 + ketamine versus placebo + ketamine. Results: 23 subjects were randomised and 15 completed all 4 study scanning sessions, with dropouts mainly due to scanner technical issues, intolerance to ketamine, or excessive head movement. AUT00206 was well tolerated with no serious or severe AEs attributed to study drug. Ketamine evoked rapid increases in BOLD signal in the 3 primary ROIs. In dACC, both doses of AUT00206 attenuated the effect of ketamine compared to placebo, with pairwise effects of Treatment (β= -0.72; [95% CI -1.19 to -0.25] p=0.003) for the 800mg dose and (β= -0.49; [95% CI-0.97 to -0.02] p=0.04) for the 2000mg dose. BOLD responses to ketamine in precuneus and thalamus were similar in magnitude, but shorter lasting than responses in dACC. AUT00206 did not attenuate ketamine effects in precuneus. In thalamus AUT00206 800mg lessened responses in the second 8 minutes at trend level significance (p=0.05) contributing to an overall Treatment by Time interaction (p=0.03). AUT00206 800mg attenuated ketamine effects in all 12 secondary ROIs reaching significance in insula and right prefrontal cortex, again in the last 8 minutes. Discussion: This study is the first evidence of a central effect of the novel Kv3 modulator, AUT00206 in healthy humans. Based on evidence from rodent models, we suggest that the drug enhances the activity of GABA interneurons in cortical circuits, which opposes the effects of ketamine. The results are also consistent with results from the rodent ketamine-challenge model. These results are promising for the potential use of AUT00206 in the treatment of disorders associated with reduced cortical inhibitory function, such as schizophrenia.